Hubungan prenatal yoga dengan kelancaran persalinan - Suci Arsita Sari; Sri Luluk (Indonesian Public Health-Observer Information Forum (IPHORR) Kerjasama dengan Persatuan Perawat Nasional Indonesia (PPNI), 2025)
Background: Maternal and perinatal mortality rates in Indonesia remain high, partly due to prolonged labor. Prenatal yoga can be an approach to improve birth canal muscle flexibility, breathing techniques, relaxation, and maternal mental calmness during labor. Purpose: To analyze the relationship between prenatal yoga implementation and smooth delivery. Method: This research used a correlational analytic method with a case control approach. The population included all women giving birth in Bi'rali 3 room, 'Aisyiyah Hospital Bojonegoro, with a monthly rate of 35 people in 2024. The sample comprised of 35 respondents selected through accidental sampling. Data was collected using questionnaires and analyzed using Chi-Square after editing, coding, scoring, and tabulating. Result: The research results showed that out of 25 women in labor who participated in prenatal yoga, the majority experienced smooth second stage labor, accounting for 24 respondents (96.0%). Based on the Chi-Square statistical test, the ρ value = 0.000 < α (0.05) was obtained, thus H0 is rejected, indicating there is a relationship between prenatal yoga and smooth second stage labor. Conclusion: The study concluded that there is a relationship between prenatal yoga implementation and smooth delivery. Suggestion: Pregnant women are encouraged to consider prenatal yoga as part of their birth preparation, seek information about prenatal yoga classes at nearby health facilities, and consult medical professionals before starting the program.